Analysis of Halal Literacy, Halal Awareness, Motivation and Religiousity of SMES on Interest in Halal Certification in Banjarmasin - Wahab, Abdul Wahab; Iman Setya Budi; Amanda, Afina Putri Fatimah (Universitas Muhammadiyah Surakarta, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) play a significant role in Banjarmasin City's local economic development. Along with this growth, halal products have great potential to gain the support of consumers whose awareness of halal products is increasing. Halal factors are becoming increasingly important to consumers when making routine product purchases. This study examines how the motivation,religiosity, halal literacy, and halal awareness of MSME (Micro, Small, and Medium Enterprises) actors affect their desire to get halal certification in Banjarmasin City. This study is conducted using field research using a quantitative descriptive technique. Purposive sampling, a non-probability sampling technique, selects samples based on the requirement to meet specific objectives, such as identifying MSMEs in Banjarmasin for a minimum of one year. A questionnaire is used for data collection, and the sample size is 96. Using SPSS 25.0 for Windows applications,the following data analysis procedures were employed: hypothesis testing, data validity analysis, and descriptive data analysis. The findings indicate that MSMEs' interest in Halal Certification in Banjarmasin City is significantly influenced, at least in part, by the factors of Halal Literacy, Halal Awareness, Motivation, and Religiosity. The factors significantly impacting MSMEs' interest in halal certification in Banjarmasin City simultaneously include motivation,religiosity, halal literacy, and halal awareness.